(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Gandhi fought for the advancement and liberation of India. He became a prolific writer who impacted authors and academics in various subjects, including politics, literature, sociology, history, philosophy, and more. Notable Indian writers explored Gandhian ideas. Their books are based on the philosophy of Mahatma Gandhi, including his beliefs on untouchability, nonviolence, truth, brotherhood, and satyagraha. The paper aims to investigate the Gandhian strain in multilingual Indian writers.